2004
DOI: 10.1021/bi035900h
|View full text |Cite
|
Sign up to set email alerts
|

Homooligomerization of the Cytoplasmic Domain of the T Cell Receptor ζ Chain and of Other Proteins Containing the Immunoreceptor Tyrosine-Based Activation Motif

Abstract: Antigen receptors on T cells, B cells, mast cells, and basophils all have cytoplasmic domains containing one or more copies of an immunoreceptor tyrosine-based activation motif (ITAM), tyrosine residues of which are phosphorylated upon receptor engagement in an early and obligatory event in the signaling cascade. How clustering of receptor extracellular domains leads to phosphorylation of cytoplasmic domain ITAMs is not known, and little structural or biochemical information is available for the ITAM-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
184
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(202 citation statements)
references
References 72 publications
16
184
2
Order By: Relevance
“…Considering the unstructured nature of ζ cyt , the question as to whether the protein remains disordered or undergoes a structural transition to a folded form in the ζ cyt dimer is of fundamental importance. According to our previously reported circular dichroic data [7], specific dimerization of ζ cyt does not induce detectable secondary or tertiary structure. Because of the high sensitivity of NMR chemical shifts to structural changes at atomic resolution not detected with optical methods, NMR spectroscopy is unparalleled in its ability to provide detailed structural information on unfolded proteins [9].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Considering the unstructured nature of ζ cyt , the question as to whether the protein remains disordered or undergoes a structural transition to a folded form in the ζ cyt dimer is of fundamental importance. According to our previously reported circular dichroic data [7], specific dimerization of ζ cyt does not induce detectable secondary or tertiary structure. Because of the high sensitivity of NMR chemical shifts to structural changes at atomic resolution not detected with optical methods, NMR spectroscopy is unparalleled in its ability to provide detailed structural information on unfolded proteins [9].…”
Section: Introductionsupporting
confidence: 60%
“…Signaling through the ζ chain is mediated by a triplicate of conserved cytoplasmic sequence motifs, termed Immunoreceptor Tyrosine-based Activation Motifs (ITAMs), where tyrosine residues are phosphorylated upon TCR engagement in an early and obligatory event in the signaling cascade. We and others have previously reported that the 13-kDa ζ cyt oplasmic domain (ζ cyt ) is intrinsically disordered [6][7][8]. Recently, we have found that this protein shows clear signs of specific dimerization [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, a striking difference between the two families is observed in structural patterns of intracellular signal-generating regions. Recently, using a variety of biophysical techniques 1,4,9 and prediction algorithms, 3,5 we found that while signaling by SRs is mediated through intracellular well-defined protein structures (Fig. 1) [10][11] (4) The modular assembly of MIRRs (Fig.…”
Section: Cell Receptors Signal Through Protein Disorder or Order Depmentioning
confidence: 99%
“…Recent findings show that while ligand binding outside the cell is mediated through well-structured protein domains, intracellular signaling domains of many receptors represent intrinsically disordered regions (IDRs), the regions that lack a well-defined three-dimensional structure under physiological conditions. [1][2][3][4][5] Intriguingly, protein intrinsic disorder is a characteristic feature of the cytoplasmic signaling domains of those receptors, in which recognition and signaling are mediated by separate protein chains. 1,4,5 Our studies of these signaling-related IDRs reveal several unusual and previously unreported biophysical phenomena 1,4,[6][7][8][9] that not only facilitate a rethinking process of the fundamental paradigms in protein biophysics but also open new perspectives on the molecular mechanisms of receptor signaling with multiple applications in biology and medicine.…”
Section: Introductionmentioning
confidence: 99%